Phenomenon of mission in the companies in Serbia - Gavric, Gordana; Kirin, Snežana; Fedajev, Aleksandra; Talović, Violeta (Serbian Journal of Management, 2018)
Mission statement is personification of organizational identity and serve as central point for individual which identify themselves with the organization. Well-defined mission ensures the stability of an organization as it gives clear direction and is an important factor of cohesion. The behavior of employees, caused by this mission, is important for achieving the end results in business, and is therefore rightly considered to be a powerful tool in the management of an organization. The study’s aim is to show, through empirical research, how many employees are familiar with the mission of company they work for, and to point out the differences in understanding of the mission that exist among employees in public and private companies in Serbia. For the purpose of this research a questionnaire was constructed according to Denison model and was distributed in direct contact with respondents and via social network Facebook. Collected data were statistically analyzed and interpreted using descriptive analysis and independent samples test. The results showed that companies in Serbia still need to work on informing employees with mission and that there is significant difference between state and private companies in that sense.